PREVALENCE OF CONGENITAL COLOUR VISION DEFICIENCY AMONG SECONDARY SCHOOL MALE STUDENTS IN ALMADINA ALMUNAWARA (SAUDI ARABIA) - Al-Ghamdi AK; Al-Harbi Z; Al-Ghamdi KS (Malaysian Journal of Public Health Medicine, 2018)
The aim of this cross-sectional study is to determine the prevalence of congenital colour vision defects among male secondary school students in Al-Madinah Al-Munawara city, Saudi Arabia. A total of 1154 male secondary school students were selected randomly through a multi-stage sampling method. Ishihara 24-plates was used to screen for colour blindness. The overall prevalence of congenital colour vision defects was 3.3% with 1% protanopes and 2.3% deuteranopes. The prevalence of congenital colour vision defect among Saudis was 2.48% and (5.48%) among non-Saudis. In conclusion, the prevalence of congenital colour vision defect among male secondary school students of Al-Madinah Al-Munawara city is comparable to previously reported in central Saudi Arabia, but lower than for Caucasian.